Postoperative analgesia in elderly patients with frailty syndrome - O.A. Halushko; L.M. Zenkina; M.Y. Mohammad (Bolʹ, Sustavy, Pozvonočnik, 2025)
Background. The increase in the proportion of elderly people on the planet has led to a proportional increase in elderly patients undergoing surgical treatment. Elderly surgical patients often develop geriatric syndromes, one of which is the “frailty syndrome” (FS). The purpose. Based on the analysis of scientific literature, highlight the features of postoperative analgesia in patients with FS. Materials and methods. To achieve the goal, a search and analysis of full-text articles in the PubMed, Web of Science, Google Scholar, Scopus databases were conducted. The search was conducted using the key terms “frailty syndrome” and “postoperative analgesia”, including randomized controlled trials and meta-analyses, and covered English- and Ukrainian-language publications over the past 10 years (from December 2014 to December 2024). Results. A total of 262 publications were identified and analyzed. As the analysis of sources showed, for postoperative analgesia in patients with FS, the method of assessing the pain syndrome and the rational selection of drugs for analgesia in these patients are of great importance. To assess the severity of pain in patients with FS, it is worth using the Facial Pain Scale and the Defense and Veterans Pain Assessment Scale. When choosing an analgesia method, it should be taken into account that ageing affects the pharmacokinetics and pharmacodynamics of drugs. Therefore, the doses of most modern analgesics in patients with FS should be reduced by 25–75 %. Namely, analgesia should be carried out under conditions of careful cardio-respiratory monitoring. Conclusions. In patients with FS, the pain management plan in the postoperative period should include a thorough assessment of the pain syndrome and a course of postoperative treatment with adequate pain relief. For most analgesia strategies, the concept of “start with the lowest possible dose and increase slowly” should be applied.